2008
DOI: 10.1038/ejhg.2008.153
|View full text |Cite
|
Sign up to set email alerts
|

Compound heterozygosity for two MSH2 mutations suggests mild consequences of the initiation codon variant c.1A>G of MSH2

Abstract: Mono-allelic germline mutations in mismatch repair (MMR) genes lead to Lynch syndrome, an autosomal dominant syndrome with an increased risk of predominantly colorectal and endometrial cancers. Bi-allelic germline mutations in MMR genes predispose to haematological malignancies, brain tumours, gastrointestinal tumours, polyposis and features of neurofibromatosis type 1 in early childhood. We report a brother and a sister with bi-allelic germline mutations in MSH2; a pathogenic deletion of the first 6 exons and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…This may be partly due to the fact that the group of MLH1 / MSH2 biallelics contains two siblings compound heterozygous for the hypomorphic MSH2 mutation c.1A>G and a deletion encompassing exons 1–6 of this gene (c.1-?_1076+?del). These patients developed multiple LS-associated tumours in their fourth and fifth decades of life 19. Excluding these two siblings, the differences between the genetic groups are more obvious (5 vs 8 and 10 years).…”
Section: The Clinical Phenotype Of Cmmrd As Deduced From the Known Casesmentioning
confidence: 94%
See 2 more Smart Citations
“…This may be partly due to the fact that the group of MLH1 / MSH2 biallelics contains two siblings compound heterozygous for the hypomorphic MSH2 mutation c.1A>G and a deletion encompassing exons 1–6 of this gene (c.1-?_1076+?del). These patients developed multiple LS-associated tumours in their fourth and fifth decades of life 19. Excluding these two siblings, the differences between the genetic groups are more obvious (5 vs 8 and 10 years).…”
Section: The Clinical Phenotype Of Cmmrd As Deduced From the Known Casesmentioning
confidence: 94%
“…The remaining four patients had colorectal adenomas when they were young adults. Only four patients were older than 25 years when they were diagnosed with their first tumour; in all four cases a CRC 13 19 41. These four patients carried at least one allele a likely hypomorphic MSH2 , MSH6 and PMS2 mutation, respectively, and, therefore, may genetically as well as clinically represent an intermediate phenotype between CMMRD and LS.…”
Section: Suggestions Of the European Consortium ‘Care For Cmmrd’mentioning
confidence: 96%
See 1 more Smart Citation
“…First, initiation codon variants such as c.3G4A identified in this study, have been widely suggested to be a disease causing mutations. 19 Second, small in frame deletions usually cause protein misfolding and instability and this suggested that they will be disease causing mutations. 20 The c.169_171del (p.V57del) mutation identified in this study might also lead to protein misfolding, because it is located between two conserved amino acids, one branched (valine) and one polar (threonine).…”
Section: Mutation Spectrum In Han and Other East Asian Populationsmentioning
confidence: 99%
“…It is also likely that analysis of considerably large datasets will be required to better define the presentation phenotype of co-occurring mutations, especially for compound heterozygosity of two variants in the same gene that are associated with only moderately reduced function. Indeed, there is evidence that some compound heterozygote mutation carriers have considerably milder phenotype than others [20,21]. The issue of co-occurrence may be further complicated by the formation of heterodimer complexes between the different MMR proteins.…”
Section: Multifactorial Approaches To Variant Classificationmentioning
confidence: 99%